P PENGARUH TIME MANAGEMENT TERHADAP PRESTASI MAHASISWA PENDIDIKAN MATEMATIKA UIN SUSKA RIAU - Zahrotul Latifa; Granita (Program Studi Tadris Matematika Fakultas Tarbiyah Institut Agama Islam Al-Qolam Malang, 2025)
This study aims to analyze the effect of time management on the learning achievement of Mathematics Education students at UIN Suska Riau. In the world of higher education, many students face difficulties in managing time effectively, which has an impact on the quality of their learning. The method used in this study is a quantitative approach with a descriptive design. The research sample consisted of 37 students who filled out a questionnaire containing 24 statement items related to time management, including the ability to set goals, priorities, make schedules, minimize distractions, and delegate tasks. The results of the analysis using the Spearman test showed that the correlation coefficient value between time management and learning achievement was -0.069, with a significance value of 0.684, which was far above the threshold of 0.05. This finding indicates that there is no significant relationship between the two variables. Therefore, time management is not a key factor influencing academic achievement, and other variables that can contribute to student learning achievement need to be considered